Análise da responsabilidade civil de influenciadores digitais por promoverem o “cancelamento” de pessoas jurídicas - LIMA, Ana Paula Ferreira de (2023)
The internet is no longer just a communication tool and has become part of people's reality, influencing choices and shaping opinions. The present study deals with the social relations that are formed in the virtual sphere, in order to understand the arguments raised by judicial authorities to hold digital influencers responsible, when they use the right to freedom of expression to promote virtual lynching and violate the right to integrity morals of legal persons. For that, it was necessary to understand not only the freedom of expression of digital influencers in the virtual environment, but also the consequences of the “cancellation” of companies, an expression used to characterize the set of virtual attacks directed at a certain user. A bibliographical research on the subject was then carried out, as well as the study of cases in which digital influencers were held responsible for promoting the virtual lynching of legal entities, in order to understand the legal understanding. In view of this, it was verified that the guarantee of freedom of expression is necessary for the promotion of the democratic state, however, when exercised in a way that violates other personality rights, mainly, by influencers in their digital channels when they stimulate the culture of cancellation to reach legal entities, this causes damage to the image and honor, in an exponential way.